THE IMPLEMENTATION OF COMMUNICATIVE AND PARTICIPATORY APPROACH IN TEACHING ENGLISH FOR BUSINESS - Naela Hidayatul Mukaromah (Universitas Aki, 2020)
Teaching English as Foreign Language (EFL) is quite challenging because teachers should prepare materials properly as well as the teaching technique that will be applied in EFL classroom. The teachers should also pay attention to the communicative purpose of teaching EFL. This study investigates the application of teaching techniques and approaches done by EFL teacher. The researcher observed the teaching techniques applied by the lecturer as well as teaching learning process experienced by college students in English for Business classroom. Based on the research findings and discussions, it can be inferred that the lecturer applied Communicative Language Teaching and Participatory Technique which are involved in two different approaches in his class of English for Business. The two approaches are communicative and participatory approaches. Those two are applicable and appropriate to be conducted in the classroom of students in higher education. Further, it is suggested for EFL teachers to consider the classroom condition in deciding what teaching techniques to be applied. Further, the communicative purpose of language learning is supposed to be the main consideration for the teachers since the students are supposed to use English language communicatively in context.